ENGLISH STUDENTS' STRATEGIES TO SPEAK ENGLISH (A CASE STUDY OF SIXTH SEMESTER STUDENTS OF ENGLISH EDUCATION DEPARTMENT) THE STATE INSTITUTE FOR ISLAMIC STUDIES SULTHAN THAHA SAIFUDDIN JAMBI - Indah, Ade (Magister Pendidikan Bahasa Inggris Universitas Jambi, 2023)
This study aimed to discuss about English students’ strategies to speak English of sixth semester English Education Department of The State Institute for Islamic Studies Sulthan Thaha Saifuddin Jambi. The design of the study is Qualitative Method with a case study approach. Subjects of the study are the Sixth Semester Students of English Education Department and Faculty of Education and Teacher Training of The State Institute for Islamic Studies Sulthan Thaha Saifuddin Jambi. In the collecting of data, the researcher used Observation and Interview. The analyzing technique is the data reduction, data display and conclusion drawing. The results of the research show that most of English students have strategies applied to increase their ability to speak English. They use learning strategies from watching movies, absorb the structure of English through Silent Period and Improving Fluency. Researchers did not find the learning strategies of Native Speakers applied by English students because very difficult to find native speakers in their areas. Researchers also find difficulties faced by English students to speak English such as Pronunciation, Vocabulary and Meaning and Grammar. But researchers have also found the other difficulties faced by English students which are fearful or nervous and the lack friends / partners who want to speak English with them to increase their speaking skills.